The dynamics of infection and the persistence of immunity to A(H1N1)pdm09 virus in Israel. Issue 5 (22nd December 2012) - Weil, Merav; Shohat, Tamar; Bromberg, Michal; Bassal, Ravit; Dichtiar, Rita; Mandelboim, Michal; Sofer, Danit; Cohen, Dani; Mendelson, Ella
Abstract : Background: Influenza virus A(H1N1)pdm09 first appeared in Israel in late April 2009, disappeared in mid‐March 2010, and reappeared in late October 2010. Symptoms were mostly mild without need for medical care. Objectives: To provide targets for future pandemic preparedness and response by evaluating the dynamics and cumulative incidence of A(H1N1)pdm09 infection, the virus‐specific seroprevalence (HI antibody titer >1:40) at the height of the pandemic, during its decline and thereafter. Methods: A cross‐sectional seroepidemiological study was conducted on 6911 serum samples collected before, during, and after the pandemic. Results: Cumulative incidence of infection derived from the differences between post‐ and pre‐pandemic seroprevalence was 54·1%, 32·9%, 22·9%, 14·8%, and 6·3% in age‐groups 0–9, 10–19, 20–49, 50–79, and ≥80 years, respectively, and 28·5% for all age‐groups combined. Vaccination could have contributed at the most 4·6% to the post‐pandemic population seroprevalence. High pre‐pandemic immune response (47·4%) found in a cohort aged 15–18 year was strongly associated with birth years 1990–1993. Morbidity began to decline in mid‐November 2009 at 32·8% population seroprevalence (45% in ages 0–19 year) and stopped in March 2010 at 43·4% population seroprevalence in February 2010 (70% in ages 0–19 year). Between February and September 2010, seroprevalence declined by 12·2% allowing virus recirculation from October 2010. Conclusions: Our study provides targets for controlling future influenza pandemics in Israel. Vaccination should focus on the younger age‐groups (0–19 year) which played a key role in transmission of the A(H1N1)pdm09 due to lack of background immunity (ages 0–9 year) and high exposure rates (ages 10–19 year).